Narrative of the voyage of H.M.S. Herald during the years 1845-1851, under the command of Captain Henry Kellett : being a circumnavigation of the globe, and three cruizes to the Arctic regions in search of Sir John Franklin - Seemann, Berthold, 1825-1871. (London : Reeve and Co., 1853)
References: Howes, U.S.IANA, no. S.271. References: Eberstadt no. IV-136. The portion of the voyage from Vancouver Island to San Diego is described in v. 1, p. 95-118. The three cruises through Bering Straits are described in v. 2. Mode of access: Internet.